Multicenter european data of anatomical parameters of the anterior eye segment measured with an optical biometer - Niknahad, Ava; Son, Hyeck Soo; Auffarth, Gerd U.; Blöck, Louise; Savini, Giacomo; Coutinho, Catarina P.; Fernández, Joaquín; Łabuz, Grzegorz (Journal of Clinical Medicine, 2025)
Background/Objectives: Normative values of ocular parameters can be influenced by a variety of factors. This study evaluates the relationship of axial length (AL), anterior and posterior corneal curvature, anterior chamber, and corneal thickness variables with age, spherical equivalent (SE), and gender. Methods: A retrospective cohort study at three hospitals identified patients from June 2019 to July 2022. Eyes with no prior history of surgery and anterior segment pathology were included, with one eye per patient being examined by Pentacam AXL Wave (Oculus, Germany). Results: The 1075 patients included had a mean age of 52.9 (± 19.5 years), with 41.5% (446) identified as males. Compared to all variables, anterior chamber angle was most strongly associated with age, with a Spearman’s correlation coefficient (r) of −0.62 (p < 0.001), while AL was most strongly correlated with SE (r = −0.75, p < 0.001). The mean radius of anterior corneal curvature showed a significant positive correlation with SE (r = 0.08, p = 0.013). Between the two genders, males had larger median anterior chamber volume (157.8 versus 147.9 mm3, p < 0.001), depth (p < 0.05 internal and external), AL (24.2 versus 23.7 mm, p < 0.001), and flatter corneas (p < 0.05 anteriorly and posteriorly) compared to females. Conclusions: Age and SE were significantly negatively correlated with AL and anterior chamber parameters. While males showed longer AL and deeper and larger anterior chambers, females had steeper corneas but similar anterior chamber angles. The differences warrant considering age, SE, and gender when interpreting a patient’s examinations against normative data.
Veröffentlicht: 19. November 2025
Gesehen am 28.01.2026